Clinico-Comparative Study To Evaluate The Efficacy Of Lajjalu Taila Pichu And Jatyadi Taila Pichu In The Management Of Parikartika W.S.R. To Fissure-In-Ano - Upadhye, Vidya S; Raju, M D P; Yakkundi, R C; Pachchinavar, K H; Mohan, G Vinay (International Research Journal of Ayurveda & Yoga, 2020)
An anal fissure, commonly known as Parikartika in Ayurveda, is a split in the skin of the distal anal canal due to stretching of the anal mucosa beyond its capability. The acute fissure may heal with conservative management but once the fissure is recurrent or chronic, surgical intervention is required. Contrary to modern therapeutic modalities, Ayurveda offers safe, effective and cost effective therapeutic modalities in the management of Fissure-in-ano (Parikartika). With the aims and objectives of Evaluation of clinical efficacy of Pichu application of Lajjalu taila and Jatyadi Taila in the management of Fissure-in-ano (Both acute and chronic), the present research work has been planned. It is a clinico-comparative study where 60 patients of fissure-in-ano were taken in two groups with 30 patients in each group viz: Group I - Application of Lajjalu Taila Pichu. Group II - Application of Jatyadi Taila Pichu. Both preceded by sitz bath with luke warm water and internal administration of Anuloma Churna (Only for Constipated patients) 3-5 grams at bed time with Luke warm water. The Pichu was applied on daily basis for 7days (One week) (at OPD / IPD level) and thereafter, asked to visit the Ano-rectal clinic at an interval of 7 days for one month of follow-up. Results: After the completion of this study, when overall results on symptoms were calculated, Jatyadi Taila pichu was found better than Lajjalu Taila pichu. Jatyadi Taila pichu showed 90% relief in reducing the symptoms shown in the observation.